Prolonged stratospheric ozone loss in the 1995-96 arctic winter - Rex, Markus; Harris, Neil R.P.; Von der Gathen, Peter; Lehmann, Ralph; Braathen, Geir O.; Reimer, Eberhard; Beck, Alexander; Chipperfield, Martyn P.; Alfier, Reimond; Allaart, Marc; O'Connor, Fiona; Dier, Horst; et al. (Nature, 1997)
It is well established that extensive depletion of ozone, initiated by heterogenous reactions on polar stratospheric clouds (PSCs) can occur in both the Arctic and Antarctic lower stratosphere. Moreover, it has been shown that ozone loss rates in the Arctic region in recent years reached values comparable to those over the Antarctic. But until now the accumulated ozone losses over the Arctic have been the smaller, mainly because the period of Arctic ozone loss has not-unlike over the Antarctic-persisted well into springtime. Here we report the occurrence-during the unusually cold 1995-96 Arctic winter-of the highest recorded chemical ozone loss over the Arctic region. Two new kinds of behaviour were observed. First, ozone loss at some altitudes was observed long after the last exposure to PSCs. This continued loss appears to be due to a removal of the nitrogen species that slow down chemical ozone depletion. Second, in another altitude range ozone loss rates decreased while PSCs were still present, apparently because of an early transformation of the ozone-destroying chlorine species into less active chlorinenitrate. The balance between these two counteracting mechanisms is probably a fine one, determined by small differences in wintertime stratospheric temperatures. If the apparent cooling trend in the Arctic stratosphere is real, more dramatic ozone losses may occur in the future.